Artificial Intelligence Enabled Learning as a Driver of Workforce Readiness in Hospitality and Tourism - Santos, Janry Paul A.; Abad, Mark Alvin H. (International Review of Management and Marketing, 2026)
The integration of Artificial Intelligence-enabled learning into higher education has redefined the teaching and learning environment, especially in vocational disciplines such as hospitality and tourism. This study investigates the direct and indirect effects of Artificial Intelligence-enabled learning on workforce readiness among hospitality and tourism students in the Philippines. The psychological mediators of learning engagement and self-efficacy were examined using data from 300 students, with analyses conducted using covariance-based structural equation modeling. The study’s findings suggest that Artificial Intelligence-enabled learning enhances workforce preparedness, both indirectly and directly, by boosting learning engagement and self-efficacy. This validated mediated structural model provides theoretical insight into employability research and expands on the Artificial Intelligence-enabled learning literature in an emerging economy setting. The structural model explained 44% of the variance in workforce readiness, indicating moderate explanatory power within the proposed framework. Implications for curriculum design and workforce preparedness in hospitality and tourism education are discussed.